1984
DOI: 10.1002/aic.690300205
|View full text |Cite
|
Sign up to set email alerts
|

Selective adsorption of organic homologues onto activated carbon from dilute aqueous solutions: Solvophobic interaction approach: Part IV. Effect of simple structural modifications with aliphatics

Abstract: Preferential adsorption of organic compounds onto activated carbon from dilute aqueous solutions is studied to develop a comprehensive theoretical basis for predicting the adsorption of structurally different isomers for different homologous series. The fundamental multidimensional approach of the solvophobic (c+) thermodynamic theory is further refined and used to correlate the extent of adsorption for the comprehensive theory with the overall standard net free energy change (ACnet/RT) for the association-ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 16 publications
0
35
0
Order By: Relevance
“…Many semi-theoretical models describing the QSARs have been proposed to predict the sorption parameters including the octanol-water partitioning coefficient, the LSE model, (Nirmalakhandan and Speece, 1993;Luehrs et al, 1996), the MCI model (Blum et al, 1994;Nirmalakhandan and Speece, 1988), and the solvophobic theory (Belfort et al, 1984). While utilising the above QSARs, it is hypothesised that the sorption coefficients normalised to the organic carbon fraction of the sediment (K exp oc ) values for pollutants in fact depend upon the background ionic strength of the system and the validity of this approach has been demonstrated by incorporating the ionic strength term into the three QSARs namely octanol-water partitioning coefficient model (Kow model), the LSE model, and the MCI model.…”
Section: Estimation Of Sorption Coefficients Using Qsarsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many semi-theoretical models describing the QSARs have been proposed to predict the sorption parameters including the octanol-water partitioning coefficient, the LSE model, (Nirmalakhandan and Speece, 1993;Luehrs et al, 1996), the MCI model (Blum et al, 1994;Nirmalakhandan and Speece, 1988), and the solvophobic theory (Belfort et al, 1984). While utilising the above QSARs, it is hypothesised that the sorption coefficients normalised to the organic carbon fraction of the sediment (K exp oc ) values for pollutants in fact depend upon the background ionic strength of the system and the validity of this approach has been demonstrated by incorporating the ionic strength term into the three QSARs namely octanol-water partitioning coefficient model (Kow model), the LSE model, and the MCI model.…”
Section: Estimation Of Sorption Coefficients Using Qsarsmentioning
confidence: 99%
“…Many semi-theoretical quantitative structure activity relationships (QSARs) have been proposed to parameterise sorption onto soils/sediments (Baker et al, 1997;Meylan et al, 1992), sorption onto activated carbon (Blum et al, 1994;Luehrs et al, 1996;Belfort et al, 1984), sorption onto wastewater solids (Dobbs et al, 1989), adsorption of organic vapours onto activated carbon (Urano et al, 1982;Nirmalakhandan and Speece, 1993;Prakash et al, 1994), dissolution of compounds (Kamlet et al, 1986;Lane and Loehrs, 1995;Speece, 1988, 1989;Dunnivent et al, 1992), Henry's law constants (Nirmalakhandan and Speece, 1988;Dunnivent et al, 1992;Nirmalakhandan et al, 1997;Brennan et al, 1998), chemical biotransfer (Dowdy et al, 1996), chemical toxicity (Blum and Speece, 1990;Xu and Nirmalakhandan, 1998); and octanolwater partition coefficients (Sablijic et al, 1993). It is well known that the physico-chemical interactions depend on chemical properties of the pollutant such as aqueous solubilities, octanol/water partition coefficients, or structural characteristics including substituted groups on the pollutant molecule, molar volume of the molecule, topology as well as the intrinsic properties like polarity and polarisability of the pollutant molecules (Westall et al, 1985;Kamlet et al, 1986).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, specific studies have been carried out for washing soils/sediments contaminated with organics 2,4,15 and inorganics 1,8,9,13,16 and also modeling the sorption and desorption phenomenon. 17 Many isolated research efforts on development and application of quantitative structure activity relationships (QSARs) for predicting the sorption and desorption equilibrium at the activated carbon/water interface or activated carbon/air interface [18][19][20][21][22] have been reported in the literature. However, no studies on modeling the soil-washing techniques and incorporating the QSARs for prediction of the thermodynamic limits of sorption and desorption into the soil-washing model have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the semi-theoretical models describing the QSARs proposed to predict the sorption parameters include the octanol-water partitioning coefficient (Kow model), the linear solvation energy model (LSE model), 19,20 the molecular connectivity indices model (MCI model) 18,21 and the Solvophobic Theory. 22 Among the various QSAR formulations tried (Kow, LSE, and MCI models) for the nonionic hydrophobic organic solvents (such as BTEX), it has been concluded that the MCI group of models is the most suitable QSAR based on an elaborate goodness-of-fit exercise, χ 2 test, and standard error of estimator analyses.…”
Section: Model For Sorption Associated With Volatilizationmentioning
confidence: 99%